2011
DOI: 10.5194/cp-7-249-2011
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of a Marinoan Snowball Earth in a state-of-the-art atmosphere-ocean general circulation model

Abstract: Abstract.We study the initiation of a Marinoan Snowball Earth (∼635 million years before present) with the state-of-the-art atmosphere-ocean general circulation model ECHAM5/MPI-OM. This is the most sophisticated model ever applied to Snowball initiation. A comparison with a preindustrial control climate shows that the change of surface boundary conditions from present-day to Marinoan, including a shift of continents to low latitudes, induces a globalmean cooling of 4.6 K. Two thirds of this cooling can be att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 46 publications
8
119
3
Order By: Relevance
“…In some general circulation models, various authors also have found this characteristic to prevail (e.g. Lewis et al, 2007;Voigt and Marotzke, 2010;Voigt et al, 2011). However, in other models, it is found that a state with tropical open-water may be stable even if the sea ice edge reaches as low as 10 • latitude (Chandler and Sohl, 2000;Baum and Crowley, 2001;Pierrehumbert et al, 2011;Abbot et al, 2011;Yang et al, 2012a,b).…”
mentioning
confidence: 99%
“…In some general circulation models, various authors also have found this characteristic to prevail (e.g. Lewis et al, 2007;Voigt and Marotzke, 2010;Voigt et al, 2011). However, in other models, it is found that a state with tropical open-water may be stable even if the sea ice edge reaches as low as 10 • latitude (Chandler and Sohl, 2000;Baum and Crowley, 2001;Pierrehumbert et al, 2011;Abbot et al, 2011;Yang et al, 2012a,b).…”
mentioning
confidence: 99%
“…Lewis et al, 2007;Peltier et al, 2007;Peltier, 2010, 2011;Pierrehumbert et al, 2011). Several recent studies with fully coupled atmosphere-ocean models have suggested that the CO 2 threshold is quite strongly model dependent, ranging from 17.5-20 ppmv in CCSM3 (Yang et al, 2012a,b), 86 ppmv in MIROC-lite (Oka et al, 2010), 70-100 ppmv in CCSM4 (Yang et al, 2012c), to 278 ppmv in ECHAM5/MPI-OM (Voigt and Marotzke, 2010;Voigt et al, 2011), when there is a 6 % reduction in solar luminosity. For deglaciation is assumed, simulations with different models have also suggested different thresholds (Hyde et al, 2000;Tajika, 2003;Pierrehumbert, 2004Pierrehumbert, , 2005Le Hir et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More energy leaves the atmosphere at the top than enters at the bottom, yet the snowball planet does not cool off, implying that there is a small spurious heat source in the model atmosphere. This discrepancy, which may be a surface diagnostic bug rather than a true model error, was noted by Voigt et al (2011) and should not significantly affect our results, since we only compare time variations in thermal emission. We simply renormalize the snowball simulation's thermal emission to the time-averaged absorbed power in Sections 3 and 4 of this paper.…”
Section: Time-averaged Power Budgetmentioning
confidence: 88%
“…A detailed description of the GCM is given in Voigt et al (2011), and references therein. We use topof-atmosphere (TOA) incident stellar flux, outgoing longwave radiation, and reflected light, each of which is outputted every two hours at each grid point.…”
Section: Global Climate Modelsmentioning
confidence: 99%
See 1 more Smart Citation